Sustainable Disaster Adaptive Food Security Strategies Based on Spatial Analysis and Stakeholder Prioritization - Rizal Ichsan Syah Putra Rizal; Chairunisa Nur Rarastiti; Nely Zulfa (Journal of Global Sustainable Agriculture, 2026)
The City of Semarang routinely faces flood disasters that threaten food security. This study aims to formulate a flood-adaptive food security strategy using a multidisciplinary approach. The methodology integrates three main analyses: Geographic Information System (GIS) mapping for flood vulnerability using spatial data overlay (including 2025 land cover update); quantitative impact analysis on household food security by comparing the Food Consumption Score (FCS) between affected (case) and non-affected (control) areas; and strategic priority determination using the Analytical Hierarchy Process (AHP) involving seven key stakeholders. The spatial analysis results indicate that northern coastal areas, such as Genuk and North Semarang Districts, have the highest flood vulnerability. The comparative FCS analysis confirmed that flooding significantly reduces food security, evidenced by a 36.5% decrease in the average FCS score and the emergence of 20% of households in the food-insecure category in case areas. The AHP prioritization established Food Stability (weight 0.329) and Food Access (weight 0.276) as the two highest priority criteria. The synthesis of these analyses yields a sustainable city strategy prioritizing concrete interventions such as developing communal food barns for emergency reserves, establishing disaster-resilient alternative logistics routes, and protecting productive agricultural land. Overall, this research provides a strong scientific basis for the Semarang City Government to design effective disaster mitigation policies inherently integrated with long-term efforts toward achieving a resilient and sustainable food system.